2018
DOI: 10.1155/2018/8231547
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Identifies One De Novo Variant in theFGD6Gene in a Thai Family with Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) has a strong genetic basis, although the genetics of autism is complex and it is unclear. Genetic testing such as microarray or sequencing was widely used to identify autism markers, but they are unsuccessful in several cases. The objective of this study is to identify causative variants of autism in two Thai families by using whole-exome sequencing technique. Whole-exome sequencing was performed with autism-affected children from two unrelated families. Each sample was sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…in recent years, remarkable progress has been made towards understanding the genetic risks of autism using WES (22,23). For example, some de novo mutations were found by comparing the WeSs of sporadic cases with those of their parents (17,(24)(25)(26)(27)(28)(29). it has been suggested that these de novo mutations can increase the risk of autism but may not lead to autism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in recent years, remarkable progress has been made towards understanding the genetic risks of autism using WES (22,23). For example, some de novo mutations were found by comparing the WeSs of sporadic cases with those of their parents (17,(24)(25)(26)(27)(28)(29). it has been suggested that these de novo mutations can increase the risk of autism but may not lead to autism.…”
Section: Discussionmentioning
confidence: 99%
“…it has been suggested that these de novo mutations can increase the risk of autism but may not lead to autism. Therefore, it is necessary to perform a WeS study based on the family pedigree of aSd patients to explore possible hereditary mutations (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some copy number variations (CNVs) may have been associated with the increased risk of developing ASD ( Bernier et al, 2016 ; Zarrei et al, 2019 ; Bauleo et al, 2021 ; Costa et al, 2022 ). A recent whole-exome sequencing study identified one de novo causative variant (c.2951G>A) in the FGD6 gene (OMIM ID: 613520) in Thai ASD patients ( Thongnak et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the selection of de novo missense mutations has become a problem requiring further investigation. Relevant software programs (e.g., SIFT [Sorting Intolerant From Tolerant], MutationTaster) have been used to assess the harmfulness and conservation of gene mutation sites (Thongnak et al 2018 (Li et al 2016), which prioritize the list of genes depending on the impact of mutations and assess the tolerance of genes to genetic mutations, have also been used. However, the relationship between genes and phenotypes has not been analyzed or predicted.…”
Section: Introductionmentioning
confidence: 99%